2013
DOI: 10.1371/journal.pone.0070191
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide Reductase Large Subunit M1 Predicts Poor Survival Due to Modulation of Proliferative and Invasive Ability of Gastric Cancer

Abstract: ObjectivesWe aimed to investigate the prognostic value of RRM1 in GC patients.MethodsA total of assessable 389 GC patients with clinicopathological and survival information were enrolled from City of Hope (COH, n = 67) and Zhejiang University (ZJU, n = 322). RRM1 protein expression was determined by immunohistochemistry on FFPE tissue samples. Kaplan-Meier and Cox analyses were used to measure survival. Ras/Raf activity and invasion assays were used to evaluate the role of RRM1 in GC cell lines.Results In vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…To normalize the reaction conditions, all FFPE tissue samples were reassembled into multiple tissue arrays as we previous reported [38]. …”
Section: Methodsmentioning
confidence: 99%
“…To normalize the reaction conditions, all FFPE tissue samples were reassembled into multiple tissue arrays as we previous reported [38]. …”
Section: Methodsmentioning
confidence: 99%
“…Studies have indicated that RRM1 is a tumor suppressor (Figure 2) [65]; therefore, high RRM1 expression is a predictor of better survival [7678]. In contrast, other studies have found that high RRM1 expression leads to poor survival [78, 79]. In fact, one study found that depending on what treatment patients received, high RRM1 expression was inconclusive for patient prognosis [80].…”
Section: Nucleotide Metabolism In Cancermentioning
confidence: 99%
“…Patients with low tumor RRM1 expression assessed using either qRT‐PCR or IHC survived 3.94 months longer (95% CI, 2.15–5.73; P  =   0.001) than those patients with high RRM1 expression. Meanwhile, RRM1 expression has been shown to be a powerful predictor of survival or chemotherapy susceptibility in patients with carcinomas, such as pancreatic cancer 23, advanced nasopharyngeal carcinoma 24, and gastric cancer 25, treated with adjuvant gemcitabine‐based chemotherapy. Since the specimen of core needle biopsies derived from patient tumors are always inconvenient to obtain, and the technologies of immunohistochemical methods, mRNA expression and quantitative in situ protein analyses, are complicated, it is necessary to identify a more generally applicable methodology.…”
Section: Discussionmentioning
confidence: 99%